Quizizz As Interactive and Gamified Assessment Platform: Voices form Indonesian EFL Secondary Learners - Moh. Ilham Dzikrullah; Ahmad Syafi'i (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
Almost every aspect of human life on earth has been disrupted since the emergence of Covid-19, particularly education. Many countries have decided to close schools and universities. This condition has forced the Indonesian government through its Ministry of Education to implement policies that move conventional classrooms to online classrooms. This process is carried out to maintain the health of students. The learning process has been aided by the use one of applications available on the internet called Student Response System (SRS). This study investigates secondary school students’ perceptions towards the implementation of Quizizz as an assessment platform in teaching English. Mixed-method research has been implemented in this study. The study involved 61 students as the participants in the quantitative stage and six students in the qualitative stage. The main instruments employed in this research are an online questionnaire and in-depth interview. The findings indicated that the students have both positive and negative perceptions toward the use of online assessment, especially Quizizz. The students enjoyed Quizizz and thought it was exciting, interesting, motivating, and enjoyable because it was distinct from other platforms. Quizizz had an interactive display, which made it simple for students to use. However, in addition to the positive perception of Quizizz as an assessment platform in English teaching, some students expressed a negative perception of Quizizz as an assessment tool. According to the data, one of the platform’s negative perceptions was the presence of music.Hampir setiap aspek kehidupan manusia di muka bumi ini terganggu sejak munculnya Covid-19, khususnya pendidikan. Banyak negara telah memutuskan untuk menutup sekolah dan universitas. Kondisi ini memaksa pemerintah Indonesia melalui Kementerian Pendidikan untuk menerapkan kebijakan pemindahan ruang kelas konvensional menjadi ruang kelas daring. Proses ini dilakukan untuk menjaga kesehatan siswa agar terhindar dari Covid-19. Proses pembelajaran dapat dibantu dengan menggunakan salah satu aplikasi di internet yang bernama Student Response System (SRS). Menurut pernyataan tersebut, peneliti menyelidiki persepsi siswa sekolah menengah terhadap penerapan Quizizz sebagai platform penilaian dalam pengajaran bahasa Inggris. Penelitian metode campuran telah diterapkan dalam penelitian ini. Penelitian ini melibatkan 61 siswa sebagai partisipan pada tahap kuantitatif dan 6 siswa pada tahap kualitatif. Instrumen utama yang digunakan dalam penelitian ini adalah kuesioner online dan wawancara mendalam. Temuan menunjukkan bahwa siswa memiliki persepsi positif dan negatif terhadap penggunaan penilaian online, terutama di Quizizz. Para siswa menikmati Quizizz dan menganggapnya menyenangkan, menarik, memotivasi, dan menyenangkan karena platform Quizizz berbeda dari yang lain. Quizizz memiliki tampilan interaktif, yang memudahkan siswa dalam menggunakan platform. Namun, selain persepsi positif tentang Quizizz sebagai platform penilaian dalam pengajaran bahasa Inggris, beberapa siswa menyatakan persepsi negatif tentang Quizizz sebagai penilaian. Menurut data, salah satu persepsi negatif platform adalah kehadiran musik.